The Correlation Between Surface Scaling Behavior and Optical Properties of Nio Thin Films Nanostructures: An Investigation Based on Fractal Concepts - Escrig-Murua, J (Elsevier Ltd, 2024)
Here, we report room temperature deposition of nickel oxide (NiO) thin films on silicon and glass substrates by direct current (dc) magnetron sputtering using a metallic nickel target. The effect of sputtering power (20 W, 25 W, and 30 W) on the thin films, their surface scaling, fractal dimension, and optical properties are extensively investigated. Autocorrelation and height–height correlation functions were applied to AFM images to extract deep insights about the thin films surfaces. Fractal dimension (Df) was extracted through the power spectral density (PSD) function. Various scaling exponents, including α, β, and 1/z, of the NiO film s surface were independently observed. The local roughness exponent, α, was approximately 0.81 for films deposited with 20 W sputtering power and decreased to 0.71 with higher sputtering power. The interface width (σ) scales with sputtering power (Sp) as ∼ Spβ, with a growth exponent (β) value of 1.17. The lateral correlation length (ξ) follows as ∼ Sp1/z with a 1/z value of 0.703. Additionally, optical parameters were recorded through UV–Vis. optical spectroscopy, and an attempt was made to correlate them with fractal parameters (Df & α). Optical absorption (reflection) increased (decreased) with increasing Df values. The minimum (maximum) reflection (absorption) was observed on the roughest surface (Df = 2.29). The calculated band gap decreased with increasing fractal dimension. This investigation suggests that sputtered surfaces with minimal reflectivity, band gap, and enhanced light-absorbing capacity could potentially be used as active solar layers for advanced optoelectronic devices. © 2024 Elsevier Ltd and Techna Group S.r.l.